A phase II study of the insulin-like growth factor type I receptor inhibitor IMC-A12 in patients with metastatic uveal melanoma. Issue 6 (December 2020) - Mattei, Jane; Ballhausen, Alexej; Bassett, Roland; Shephard, Michael; Chattopadhyay, Chandrani; Hudgens, Courtney; Tetzlaff, Michael; Woodman, Scott; Sato, Takami; Patel, Sapna P.
Abstract : Uveal melanoma is a rare and aggressive malignancy and up to half of all patients will develop metastatic disease despite the effective treatment of the primary tumor. Insulin-like growth factors I/II play a fundamental role in the cell migration, proliferation, and apoptosis. IMC-A12, a mAb specifically targets insulin-like growth factor type I receptor, has shown promise in preclinical studies. We performed a multicenter phase II study for patients with metastatic uveal melanoma administered IMC-A12 10 mg/kg IV every two weeks until disease progression or unacceptable toxicity. The primary endpoint was objective response (proportion of patients with complete or partial response), and secondary endpoints were disease control rate, progression-free survival, and overall survival. A total of 18 patients enrolled in this study (10 males and eight females) with a median age. Ten patients (55%) had stable disease, seven patients (38%) had progression as best overall response. No partial response or complete response was observed; however, the disease control rate, defined as complete response + partial response + stable disease ≥3 months, was 50%. Median progression-free survival was 3.1 months, and median overall survival was 13.8 months. Adverse events of any grade occurred in 13 patients (72.2%). Treatment-related grade 3 adverse events were rare, and there were no grade 4 or 5 related adverse events. IMC-A12 was very well tolerated, however, showed limited clinical activity in uveal melanoma as a single agent. Due to its low toxicity profile it could be studied in combination with other pathway-specific agents.